Counterfactual cognitive deficit in persons with Parkinson's disease. Issue 8 (21st July 2003) - McNamara, P; Durso, R; Brown, A; Lynch, A
Abstract : Background: Counterfactuals are mental representations of alternatives to past events. Recent research has shown them to be important for other cognitive processes, such as planning, causal reasoning, problem solving, and decision making—all processes independently linked to the frontal lobes. Objective: To test the hypothesis that counterfactual thinking is impaired in some patients with Parkinson's disease and is linked to frontal dysfunction in these patients. Methods. Measures of counterfactual processing and frontal lobe functioning were administered to 24 persons with Parkinson's disease and 15 age matched healthy controls. Results. Patients with Parkinson's disease spontaneously generated significantly fewer counterfactuals than controls despite showing no differences from controls on a semantic fluency test; they also performed at chance levels on a counterfactual inference test, while age matched controls performed above chance levels on this test. Performance on both the counterfactual generation and inference tests correlated significantly with performance on two tests traditionally linked to frontal lobe functioning (Stroop colour–word interference and Tower of London planning tasks) and one test of pragmatic social communication skills. Conclusions: Counterfactual thinking is impaired in Parkinson's disease. This impairment may be related to frontal lobe dysfunction.